2015
DOI: 10.1186/s40200-015-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predisposing, reinforcing and enabling factors on self-care behaviors of the patients with diabetes mellitus in the Minoodasht city, Iran

Abstract: BackgroundTo control diabetes mellitus (DM) it is necessary to make overall changes in the life style of the patients. The aim of this study was to determine the effects of predisposing, reinforcing and enabling factors on self-care behaviors of the patients with DM in the Minoodasht city, Iran in 2012.MethodsIn this quasi-experimental study, 78 people with DM were selected by convenience sampling method. In the first stage of study, the educational program was compiled and executed on six information sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
3
9
0
1
Order By: Relevance
“…The effect of the health educational intervention guidelines was confirmed by the regression analysis, which determined the intervention as a main independent predictor of the improvement of knowledge. The finding is in agreement with Abdo and Mohamed (2010) [36] in Egypt and Borhani et al (2015) [37] in Iran, who reported a similar success of an educational intervention for T2DM patients. Also in line with the current study results, Lewis et al (2015) [38] in a study in the United States revealed a retention of the post-intervention improvement in patients' knowledge at follow-up testing.…”
Section: Discussionsupporting
confidence: 83%
“…The effect of the health educational intervention guidelines was confirmed by the regression analysis, which determined the intervention as a main independent predictor of the improvement of knowledge. The finding is in agreement with Abdo and Mohamed (2010) [36] in Egypt and Borhani et al (2015) [37] in Iran, who reported a similar success of an educational intervention for T2DM patients. Also in line with the current study results, Lewis et al (2015) [38] in a study in the United States revealed a retention of the post-intervention improvement in patients' knowledge at follow-up testing.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the relationship between the contact time and reducing glycohemoglobin, there are studies that show a lack of relationship between these variables (4,9) . These studies, however, have determined what features of interventions have the greatest effect on glycemic control, and among them is the contact time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have pointed out, among their key findings, the benefits obtained by educational interventions in the treatment and control of diabetes mellitus. The importance of considering the knowledge, attitudes, and care practices with diabetes as constituting skills also stands out, so that one can understand the behavior observed and guide its change (8)(9) . Thus, the contact time variable becomes feasible for measuring the association with the skills needed to control diabetes mellitus, thus verifying the influence on users' self-care practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations